2020
DOI: 10.1101/gr.261586.120
|View full text |Cite
|
Sign up to set email alerts
|

Large tandem duplications affect gene expression, 3D organization, and plant–pathogen response

Abstract: Service Email Alerting click here. top right corner of the article or Receive free email alerts when new articles cite this article-sign up in the box at the http://genome.cshlp.org/subscriptions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 70 publications
0
33
0
Order By: Relevance
“…A large number of orthologous genes indicated the evolution of these genes could be possibly by whole genome segmental duplication events. The large numbers of gene duplications could be possibly facilitated by gene expression, gene organization and plant-pathogen response [59,60]. Moreover, the CmDIR, CsDIR and ClDIR, exhibited several orthologous genes, implying these genes had undergone nonfunctionalization, subfunctionalization, or neofunctionalization [61,62].…”
Section: Wide Distribution Of Dir On Different Chromosomes and The Romentioning
confidence: 99%
“…A large number of orthologous genes indicated the evolution of these genes could be possibly by whole genome segmental duplication events. The large numbers of gene duplications could be possibly facilitated by gene expression, gene organization and plant-pathogen response [59,60]. Moreover, the CmDIR, CsDIR and ClDIR, exhibited several orthologous genes, implying these genes had undergone nonfunctionalization, subfunctionalization, or neofunctionalization [61,62].…”
Section: Wide Distribution Of Dir On Different Chromosomes and The Romentioning
confidence: 99%
“…Investigations of the phenotypic consequences from rDNA copy number variation have uncovered a broad range of cellular processes in diverse species. While ribosome deficiencies do result when rDNA copy number drops below a threshold (Delany et al, 1994;French et al, 2003;Ritossa and Atwood, 1966;Sanchez et al, 2017), several other phenotypes have been associated recently with more physiologically relevant rDNA copy number variants that are sufficient for ribosome biogenesis (Gibbons et al, 2014;Ide et al, 2010;Lu et al, 2018;Michel et al, 2005;Paredes et al, 2011;Picart-Picolo et al, 2020;Wang and Lemos, 2017;Xu et al, 2017). Additionally, the plastic nature of the rDNA locus allows copy number fluctuations in the face of stressors such as nutrient availability (Aldrich and Maggert, 2015) or replication defects (Ide et al, 2007;Lynch et al, 2019;Salim et al, 2017;Sanchez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the epigenetic landscape can be even more dynamic when genetic material is reshuffled (SVs and TEs) as a consequence of the applied stress. It is well known that structural variants in several plant species can generate wide phenotypic diversity (for example, The 1001 Genomes Consortium, 2016 ; Zhou et al, 2019 ; Alonge et al, 2020 ) and some of which can enable improved stress tolerance, recently demonstrated by studies such as Kalladan et al (2017) , Catacchio et al (2019) , Picart-Picolo et al (2020) . Yet, genetic mutations in methyltransferase enzymes for tuning epigenetic stability ( Shen et al, 2014 ; Sasaki et al, 2019 ), or heritable genome rearrangements catalyzed by TE insertions can contain the necessary stress-response DMRs that may function to either deteriorate fitness or for adding a newly acquired stress tolerance that allows future generations to adapt to the altered environmental condition ( Quadrana and Colot, 2016 ).…”
Section: Can Stress-response Physiology Hedge Transgenerational Methymentioning
confidence: 99%